The perceptions of consumers aged 18-30 of “lesbian” appeals in advertising - GP van Rheede van Oudtshoorn; RS ORR (Communicare)
In an over-saturated market, advertisements have become more risqué as companies vie for consumer attention and lesbian content in advertising seems to be on the increase in mainstream media. This article attempts to discover whether lesbian content in advertising elicits positive or negative consumer attitudes towards the advertisement and the brand, and to link these attitudes with the intention to purchase the product. By doing so, marketers will be able to ascertain whether this type of advertising appeal is effective or whether it offends consumers and therefore decreases product sales. The study was quantitative in nature and used descriptive research in a field setting. It was found that there is a significant correlation between tolerance of homosexuality and acceptance of lesbian content in advertising. In addition, these advertisements attracted attention and interest and were not perceived as particularly immoral, exploitive or offensive by most of the sample population. In terms of attracting attention and interest, and being memorable to consumers, advertisements containing clear lesbian interaction are more effective than those with lower levels of homoerotic t